2012
DOI: 10.1002/psc.2404
|View full text |Cite
|
Sign up to set email alerts
|

Interaction structure of the complex between neuroprotective factor humanin and Alzheimer's β‐amyloid peptide revealed by affinity mass spectrometry and molecular modeling

Abstract: Humanin (HN) is a linear 24-aa peptide recently detected in human Alzheimer's disease (AD) brain. HN specifically inhibits neuronal cell death in vitro induced by ß-amyloid (Aß) peptides and by amyloid precursor protein and its gene mutations in familial AD, thereby representing a potential therapeutic lead structure for AD; however, its molecular mechanism of action is not well understood. We report here the identification of the binding epitopes between HN and Aß(1-40) and characterization of the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 42 publications
2
40
0
3
Order By: Relevance
“…The last mL of the washing fraction was collected as a control, and the bound epitope peptides eluted by 4 × 15 min incubation with 0.1% trifluoroacetic acid. Fractions were lyophilized and purified using the ZipTip procedure [17]. For affinity testing of the synthetic epitope peptides, the samples were loaded onto the affinity columns in PBS and incubated for 2 h at 37°C.…”
Section: Proteolytic Epitope Excision and Affinity Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The last mL of the washing fraction was collected as a control, and the bound epitope peptides eluted by 4 × 15 min incubation with 0.1% trifluoroacetic acid. Fractions were lyophilized and purified using the ZipTip procedure [17]. For affinity testing of the synthetic epitope peptides, the samples were loaded onto the affinity columns in PBS and incubated for 2 h at 37°C.…”
Section: Proteolytic Epitope Excision and Affinity Characterizationmentioning
confidence: 99%
“…Epitope peptides were immobilized on gold chips as previously described [17,18] and different concentrations of the HD6 antibody injected. K D determinations were performed by using OriginPro 7.5 software with the FitMaster plug-in, providing a pseudo first order kinetic constant (k obs ).…”
Section: Saw Biosensor Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific interactions between Cystatin C and Ab (Sastre et al, 2004) and Cystatin C and SAA (Bokarewa et al, 2007) had been found experimentally and, thus, had introduced two novel Cystatin C partners. Consecutive structural experiments were performed using selective proteolytic excision and high resolution mass spectrometry (Juszczyk et al, 2009;Maftei et al, 2012;Tian et al, 2007) in order to identify the crucial binding 'hotspots' both in Ab and SAA. Surprisingly, the identified interaction site of Fb is located in the 101 IYAVPWQGTMTLSKSTC 117 hCC fragment (Juszczyk et al, 2009), whereas the identified epitope on SAA is located in 96 FCSFQIY 102 fragment (Spodzieja et al, 2013;Spodzieja et al, 2012).…”
Section: Cysc2 Cysc3mentioning
confidence: 99%
“…The identifi cation and quantifi cation of Aß peptides bound to specifi c anti-Aß antibodies were provided by the newly introduced online bioaffi nity-electrospray mass spectrometry [ 5 ]. In several further studies, proteolytic excision/extraction-mass spectrometry were successfully used for the identification of interacting Aß epitope sequences with aggregation-inhibiting polypeptides [17- Reprinted with author permission from [ 14 ] such as cystatin C [ 16 ], humanin [ 24 ], and Aß-nanobodies (single chain llama anti-ß-amyloid antibodies) providing also a potential for developing new diagnostic tools for AD as well as for designing new potential immunotherapeutic agents [ 34 ].…”
Section: Affi Nity-mass Spectrometric Approaches For Elucidation Of Amentioning
confidence: 99%